Recovery of useful chemicals from palm oil mill wastewater - Yuangsawad Ratanaporn; Na-Ranong Duangkamol; Tago Teruoki; Masuda Takao (My University, 2017)
A two-step process consisting of pyrolysis of dried sludge and catalytic upgrading of pyrolysed liquid was proposed. Wastewater from a palm oil mill was separated to solid cake and liquid by filtration. The solid cake was dried and pyrolysed at 773 K. Liquid product obtained from the pyrolysis had two immiscible aqueous and oil phases (PL-A and PL-O). Identification of chemicals in PL-A and PL-O indicated that both phases contained various chemicals with unsaturated bonds, such as carboxylic acids and alcohols, however, most of the chemicals could not be identified. Catalytic upgrading of PL-A and PL-O over ZrO2·FeOx were separately performed using a fixed bed reactor at various conditions, T = 513-723 K and mass of catalyst to feed rate = 0.25-10 h. The main components in the liquid products of PL-A upgrading were methanol and acetone whereas they were acetone and phenol in the case of PL-O upgrading. More than 15% of carbon in raw material was deposited on the catalyst. To reduce the carbon deposition, the used catalyst was treated with air at 823 K. This simple treatment could reasonably regenerate the catalyst only for the case of PL-A catalytic upgrading.
Keywords: Filtration (mathematics); Pyrolysis oil; Carbon fibers; Thermochemical Biomass Conversion Processes